2009
DOI: 10.3415/vcot-08-05-0042
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of 3.5 locking compression plate fixation to 3.5 limited contact dynamic compression plate fixation in a canine cadaveric distal humeral metaphyseal gap model

Abstract: Objective-To compare the biomechanical properties of 3.5 locking compression plate (LCP) fixation to 3.5 limited contact dynamic compression plate (LC-DCP) fixation in a canine cadaveric, distal humeral metaphyseal gap model in static axial compression and cyclic axial compression and torsion.Study Design-Biomechanical in vitro study.Sample Population-30 paired humeri from adult, medium to large breed dogs.Methods-Testing was performed monotonically to failure in axial compression on ten pairs of humeri, cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many previous studies have used clamped loading conditions. 9 , 10 , 12 14 , 16 , 21 25 This study showed that clamped loading conditions were relatively insensitive to the positioning of screws. In our experimental tests, some motion was seen from the digital image correlation, which revealed that the clamp was not completely restraining movement.…”
Section: Discussionmentioning
confidence: 74%
“…Many previous studies have used clamped loading conditions. 9 , 10 , 12 14 , 16 , 21 25 This study showed that clamped loading conditions were relatively insensitive to the positioning of screws. In our experimental tests, some motion was seen from the digital image correlation, which revealed that the clamp was not completely restraining movement.…”
Section: Discussionmentioning
confidence: 74%
“…In spite of increasing knowledge on bone healing in fractures and associated biomechanical aspects (Perren and Cordey 1980;Rahn 1982;O'Sullivan et al 1989;Hulse et al 1997;Hulse et al 2000;Gautier and Sommer 2003;Wagner 2003;Aguila et al 2005;Koch 2005;Tyler et al 2008;Zahn et al 2008;Filipowicz et al 2009;Goh et al 2009) and the increasing quality of bone implants, bone nonunion remains a frequent problem both in human and veterinary medicine (Lambiris et al 2007). It is presumed that bone regeneration and successful bone defect healing may be supported by transplantation of mesenchymal stem cells in combination with biomaterials Nečas et al 2009).…”
mentioning
confidence: 99%
“…The testing of mechanical properties of some types of fracture fixations and verification and comparison of their strength and resistance ability to various types of acting forces are currently of significant scientific interest as evidenced by some studies (Hulse et al 1997;Zahn et al 2008;Filipowicz et al 2009, Urbanová et al 2010). However, in these studies, it is not clearly defined which acting force causes eventual implant failure.…”
mentioning
confidence: 99%